Astrocyte HIV-1 Tat Differentially Modulates Behavior and Brain MMP/TIMP Balance During Short and Prolonged Induction in Transgenic Mice - Joshi, Chaitanya R.; Stacy, Satomi; Sumien, Nathalie; Ghorpade, Anuja; Borgmann, Kathleen (Frontiers in Neurology, 2020)
Despite effective antiretroviral therapy (ART), mild forms of HIV-associated neurocognitive disorders (HAND) continue to afflict approximately half of all people living with HIV (PLWH). As PLWH age, HIV-associated inflammation perturbs the balance between brain matrix metalloproteinases (MMPs) and their tissue inhibitors of metalloproteinases (TIMPs), likely contributing to neuropathogenesis. The MMP/TIMP balance is associated with cognition, learning, and memory, with TIMPs eliciting neuroprotective effects. Dysregulation of the MMP/TIMP balance was evident in the brains of PLWH where levels of TIMP-1, the inducible family member, were significantly lower than non-infected controls, and MMPs were elevated. Here, we evaluated the MMP/TIMP levels in the doxycycline (DOX)-induced glial fibrillary acidic protein promoter-driven HIV-1 transactivator of transcription (Tat) transgenic mouse model. The HIV-1 protein Tat is constitutively expressed by most infected cells, even during ART suppression of viral replication. Many studies have demonstrated indirect and direct mechanisms of short-term Tat-associated neurodegeneration, including gliosis, blood-brain barrier disruption, elevated inflammatory mediators and neurotoxicity. However, the effects of acute vs. prolonged exposure on Tat-induced dysregulation remain to be seen. This is especially relevant for TIMP-1 as expression was previously shown to be differentially regulated in human astrocytes during acute vs. chronic inflammation. In this context, acute Tat expression was induced with DOX intraperitoneal injections over 3 weeks, while DOX-containing diet was used to achieve long-term Tat expression over 6 months. First, a series of behavior tests evaluating arousal, ambulation, anxiety, and cognition was performed to examine impairments analogous to those observed in HAND. Next, gene expression of components of the MMP/TIMP axis and known HAND-relevant inflammatory mediators were assessed. Altered anxiety-like, motor and/or cognitive behaviors were observed in Tat-induced (iTat) mice. Gene expression of MMPs and TIMPs was altered depending on the duration of Tat expression, which was independent of the HIV-associated neuroinflammation typically implicated in MMP/TIMP regulation. Collectively, we infer that HIV-1 Tat-mediated dysregulation of MMP/TIMP axis and behavioral changes are dependent on duration of exposure. Further, prolonged Tat expression demonstrates a phenotype comparable to asymptomatic to mild HAND manifestation in patients.